Circuit-based Localization of Ferret Prefrontal Cortex - Duque, Alvaro (Oxford University Press, 2010)
We examined the extent of the ferret prefrontal cortex (PFC) and its reciprocal connections with the mediodorsal nucleus of the thalamus (MD) by anterograde and retrograde labeling in 6- to 14-week-old male ferrets. Our results indicate that in the ferret, as in other species, MD projects heavily to the PFC although it also projects to other cortical and subcortical structures. The MD projection to PFC terminates largely in layer IV with lighter innervation of layers II, III, V, and VI. The cells projecting back to MD are mostly in layer VI. The parvocellular component of MD projects to and receives projections from the more caudal and dorsomedial component of the PFC, whereas the magnocellular portion of MD projects to and receives projections from the more rostral and lateral component of the PFC. With these results we have localized the ferret PFC, defined as a frontal cortical region with heavy reciprocal connections with the MD.